Examining consumer's purchasing behavior of energy-efficient appliance through the lenses of theory of planned behavior and environmental factors - Muhammad Ashraf, Fauzi; Siti Aminah, Harun; Noor Suhani, Sulaiman (Emerald Publishing Limited, 2022)
Purpose: This study investigates consumer purchases of energy-efficient appliances (EEAs). The adoption of EEA would reduce the detrimental impact of the environment from the consumer behavioral perspective.